THE TENTATIVE STATEMENT OF PRINCIPLES. - Scott, D. R. (The Accounting Review, 1937)
There is a close parallelism between the development of law and the development of accounting. Both arise out of a world of concrete relations and they must maintain contact with that world or lose their strength. If there is any general criticism to be made of the tentative Statement of Principles prepared by the Executive Committee of the American Accounting Association, it is that the statement shows inadequate recognition of the fundamental principle that all accounting principles and practices must preserve a vital functional relationship to a world of changing economic facts. Roughly speaking there are three major functions served by accounts. In the order of their development, these functions are the record function, the control function and the protection-of-equities function. The control function goes back at least as far as the beginning of the practice of closing the books regularly but its major development has been of very recent date especially in connection with modern industrial accounting.